A Feasibility Study on Mobile Library Services for Public Elementary Schools - Santos, Gari Lenard; Omictin, Michael Phillip; Cancio, John Michael (Diliman, Quezon City College of Engineering, 2002)
This study aims to develop a mobile library service for public schools. The project?s main objective is to provide an adequate means of supporting schools by providing free instructional materials to them. Public elementary schools were targeted for the service since they comprised the largest percentage of the student populace in the country. In addition, the pilot province for the initial implementation was identified as Cavite due to its high student density and relatively low number of public libraries. The demand was clearly established buy such determinants as the NEAT mean percentile score and pupil-textbook ratio and showed that there is an inadequate supply of education materials in public elementary schools. Alternative modes of service for achieving the objective were deemed in adequate or too costly to implement. Planning for the capacity of the bookmobile yielded a value of 2,500 books to be carried per van, 24 school days per return visit and using overnight boxes and retrieval vans for getting returned books. After the promo tour in the first two months, normal operations will expand the coverage area of the service while purchasing additional vans to increase capacity. After the mobile library has become well-established, the whole province will then be provided the service (though at the cost of lengthening time between visits). The capacity will still be increased by van purchases but after the fifth year, it has been projected that the facility maintenance will become the primary concern rather the capacity expansion. Books and van specifications were also designed. The specific area where the project will hold its headquarters would be at Trese Martires, due to its proximity to local government offices and central location. The total cost for starting the service was at little over Php 9 million. Funding services were identified as well as alternative modes of providing income for the project. Socially, the project benefits not only the educational sector, but its employees, the communities visited, local government, and the publishers and funding institutions as well. In addition, a preliminary timeline was set up to describe its implementation. The project was found feasible in all aspects of the study
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Bookmobiles; Public services (Libraries); Participatory monitoring and evaluation (Project management)